The Role of Public Health Centers (Puskesmas) as the Gatekeeper of National Health Insurance (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
The percentages of referrals for the first level health facilities visits are coming from the health center (Puskesmas) with 16.85% at the highest and from the practicing doctors with 12.45% at the lowest. The aim of the research is to examine the efficiency the promotion, preventive and curative care quality improvement. This study used qualitative exploratory design by case study approach. The collection of data was conducted through field observations, document observation and in-depth interviews. TThe informants consisted of 4 Head of Health Center/Puskesmas, 9 cadres of integrated guiding posts (Pos Pembinaan terpadu /Posbindu) for Non-Communicable Diseases (NCDs), 9 cadres of Integrated Service Post (Pos Pelayanan Terpadu/Posyandu), 33 participants of the National Health Insurance and 23 people from community who have not joined the national health insurance scheme. The results show that mini workshops are held every month in preparing activities with a focus on the causes of most diseases in the previous month. Posyandu may reduce morbidity rate on infants and pregnant women, Posbindu for Non-communicable Diseases can prevent and control non-communicable diseases. Quality of service can improve the perception of the quality of the service and can reduce referrals to hospital.